PERSEPSI MAHASISWA UINSU TENTANG BELANJA ONLINE MELALUI APLIKASI SHOPEE - Nadya Dwinna; Nadya Dwinna Putri; Dini Lestari (EKSYA : Jurnal Ekonomi Syariah, 2023)
The large number of UIN-SU students shopping online with the Shopee application made the authors interested in knowing how UIN-SU students perceive shopping in the Shopee application and to find out what factors influence UINSU student satisfaction in shopping online in the Shopee application. So the authors raised the title of the journal UIN-SU Student Perceptions About Online Shopping Through the Shopee Application using a qualitative research method. From the data we got, on average UIN-SU students are satisfied shopping at Shopee because of the free shipping vouchers, and the ShopeePay Later feature, as well as COD. And also those who are not satisfied on average answer because the items ordered are not or do not match what is received.